Inhibition of the Glycine Receptor alpha 3 Function by Colchicine - Muñoz-Montesino, Carola; Burgos, Carlos F.; Lara, Cesar O.; Riquelme, Camila R.; Flaig, David; San Martin, Victoria P.; Aguayo, Luis G.; Fuentealba, Jorge; Castro, Patricio A.; Guzmán, Leonardo; Yévenes, Gonzalo E.; Moraga-Cid, Gustavo (Frontiers in Pharmacology, 2020)
Colchicine is a plant alkaloid that is widely used as a therapeutic agent. It is widely accepted that colchicine reduces the production of inflammatory mediators mainly by altering cytoskeleton dynamics, due to its microtubule polymerization inhibitory activity. However, other lines of evidences have shown that colchicine exerts direct actions on the function of ion channels, which are independent of cytoskeleton alterations. Colchicine is able to modify the function of several pentameric ligand-gated ion channels, including glycine receptors (GlyRs). Previous electrophysiological studies have shown that colchicine act as an antagonist of GlyRs composed by the 1 subunit. In addition, it was recently demonstrated that colchicine directly bind to the 3 subunit of GlyRs. Interestingly, other studies have shown a main role of 3GlyRs on chronic inflammatory pain. Nevertheless, the functional effects of colchicine on the 3GlyR function are still unknown. Here, by using electrophysiological techniques and bioinformatics, we show that colchicine inhibited the function of the 3GlyRs. Colchicine elicited concentration-dependent inhibitory effects on 3GlyRs at micromolar range and decreased the apparent affinity for glycine. Single-channel recordings show that the colchicine inhibition is associated with a decrease in the open probability of the ion channel. Molecular docking assays suggest that colchicine preferentially bind to the orthosteric site in the closed state of the ion channel. Altogether, our results suggest that colchicine is a competitive antagonist of the 3GlyRs.